STUDI OPTIMASI ANALISIS LOGAM CO DAN NI SECARA VOLTAMMETRI STRIPING ADSORPTIF (ADSV) UNTUK PENENTUAN LOGAM DALAM KONSENTRASI RUNUT - Putri, Raesa Pratiwi; Agustiva, Agustiva; Pratiwi, Vanella Indah; Deswati, Deswati (Program Kreativitas Mahasiswa - Penelitian, 2013)
The research of the determination of Co(II) and Ni(II) by adsorptive stripping voltammetry have been done. The method used to determine the concentration of cobalt and nickel in trace (ultra trace) with calcon for Co (II) and DMG for Ni (II) as a complexing agent. The parameters  studied were variation of calcon or DMG concentration, pH, accumulation potential and accumulation time. In this study, the optimum conditions were calcon concentration of 0.7 mM for Co (II), DMG concentration of 0.8 mM for Ni (II), pH 6 for Co (II) while pH 9 for Ni (II), accumulation potential -0.3 V and accumulation time of 70 s for the Co (II) and 220 s for the Ni (II). At optimum conditions the relative standard deviation were 0.75% and 1.54%  for Co (II) and Ni (II) respectively for  ten replicates (n= 10) measurement of 10 µg /L standard solution Co(II) and Ni (II).  The method was applied to the direct   determination of Co(II) and Ni(II) in  the Stones River water rot, tap water and sea water Bungus Padang, with recovery of 106.5% and 102%. for Co(II) and Ni(II) respectively.  Keywords: voltammetry, Stripping, adsorptive, trace concentrations.